ANALISIS PENGARUH PRODUK DOMESTIK REGIONAL BRUTO (PDRB), KESENJANGAN ANTAR DAERAH DAN PEMBIAYAAN SEKTOR PENDIDIKAN TERHADAP INDEKS PEMBANGUNAN MANUSIA (IPM) KABUPATEN/KOTA DI PROVINSI JAWA TIMUR - Muhammad Rifky Rakhmadhani (Program Studi Ekonomi Pembangunan, 2018)
This study aims to analyze Gross Regional Domestic Product, Regional Gap, Education Sector Financing and Human Development Index of Regency or City in East Java Province and to find out whether Gross Regional Domestic Product, Interregional Gap, Education Sector Financing effect Human Development Index in Regency or City in East Java Province.The data was analyzed by using Panel Data Regression. Which aims to determine the magnitude of the influence between independent variables to the dependent variable is the influence of variables of Gross Domestic Product, Regional Gap, Education Sector Financing of Human Development Index at Regency or City in East Java Province. The result of research stated that the variable of Gross Regional Domestic Product have a significant positive effect with coefficient 0.475032, Regional Gap variables have positive not significant effect with coefficient 1.818401, and variable of Education Sector Financing have positive significant effect with coefficient 9.643621 on Human Development Index at Regency or City in Province East Java.Keywords : HDI, GDP, Disparity, Financing.